Il diritto al cibo religiosamente orientato al tempo di pandemia (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. I diritti fondamentali al tempo di pandemia - 2. Il “diritto al cibo” – 3. La normativa speciale anti-epidemica sulla libertà di movimento - 4. Diritti garantiti o libertà compresse?The religion-oriented right to food during pandemic timeABSTRACT: In this historical period, the epidemiological emergency has prompted governments, both local and national, to issue a series of measures aimed at tackling the pandemic, with the consequent and inevitable compression of citizens' fundamental freedoms, in particular those regarding movement and religious freedom, on the base of the predominant right to health. In relation to these rights, the problem arises regarding the purchase of religiously oriented food or particular foods for people suffering from certain diseases or allergies. Is it worth to compress, in pandemic times, the fundamental freedom in the name of the predominant right to health? The right to health and the right to food should be to guarantee to all citizens, therefore also to those suffering from particular pathologies or those professing specific religious faith in such a way they are not forced to eat “harmful or impure” food for their psychophysical health.